Microbubble data for pesticide degradation by ozone - Jarvis, Peter (Cranfield University, 2023)
Experimental data for conventional and microbubble ozonation of water matrices containing pesticides.
Keywords: MICROBUBBLES'; 'Reaction Kinetics'